2010
DOI: 10.1257/pol.2.4.119
|View full text |Cite
|
Sign up to set email alerts
|

Short-Run Impacts of Accountability on School Quality

Abstract: In the fall of 2007, New York City began using student tests and other measures to assign each school a grade (A to F), and linked grades to rewards and consequences, including possible school closure. These grades were released in late September, arguably too late for schools to make major changes in programs or personnel, and students were tested again in January (English) and March (math). Despite this time frame, regression discontinuity estimates indicate that receipt of a low grade significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 28 publications
(21 reference statements)
4
98
1
Order By: Relevance
“…Other studies exploit discontinuities in school accountability ratings and adopt a regression discontinuity approach. They show that schools receiving low ratings subsequently showed positive conditional impacts on pupil achievement gains, with strong and substantial effects (for example, Figlio and Rouse, 2006, Chiang, 2009, Rockoff and Turner, 2010and Rouse et al, 2013.…”
Section: School Accountabilitymentioning
confidence: 99%
“…Other studies exploit discontinuities in school accountability ratings and adopt a regression discontinuity approach. They show that schools receiving low ratings subsequently showed positive conditional impacts on pupil achievement gains, with strong and substantial effects (for example, Figlio and Rouse, 2006, Chiang, 2009, Rockoff and Turner, 2010and Rouse et al, 2013.…”
Section: School Accountabilitymentioning
confidence: 99%
“…achievements (Carnoy and Loeb 2002;Koning and van der Wiel 2012), undesired side-effects of such systems range from focusing teaching effort on pupils with achievements close to tests' thresholds (Reback, 2008;Neal and Whitmore Schanzenbach, 2010;Rockoff and Turner, 2010) to the distortion of results and cheating by teachers (i.e. grade inflation ;Jacob and Levitt, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While there are many possible arguments to substantiate this assumption, one reason is that schools compete over exam results to attract students and parents -and often also the government -use them to evaluate schools (e.g. Wikström and Wikström, 2005;Reback, 2008;Neal and Whitmore Schanzenbach, 2010;Rockoff and Turner, 2010).…”
Section: Assumptionsmentioning
confidence: 99%
“…One of the most prominent examples of accountability interventions is the state-level ranking system of No Child Left Behind (NCLB) in the United States. Rockoff and Turner (2010) found that the introduction of student tests and other measures to assign each school a grade was enough to increase student achievement in New York City. Rouse, Hannaway, Goldhaber, and Figlio (2013) show that http://dx.doi.org/10.1016/j.econedurev.2017.03.007 0272-7757/© 2017 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%